A Case of Fournier’s Gangrene - Neary, Elaine (Trinity Student Medical Journal, 2005)
Fournier’s gangrene is a rare, necrotising fasciitis of the genitals and perineum caused by a mixture of aerobic and anaerobic microorganisms. The complications of this synergistic infection are multiple organ failure and death. I report a case of a gentleman who presented to Accident and Emergency with gangrenous and necrotic penile, scrotal and perineal areas. Due to the aggressive nature of this condition, early diagnosis is crucial. Treatment involves extensive soft tissue debridement and broad-spectrum antibiotics. Despite appropriate therapy, mortality is high.